Medial cerebellar nuclear projections and activity patterns link cerebellar output to orofacial and respiratory behavior - Lu, Lianyi; Cao, Ying; Tokita, Kenichi; Heck, Detlef H.; Boughter, John D. (Frontiers in Neural Circuits, 2013)
There is ample evidence that the cerebellum plays an important role in coordinating both respiratory and orofacial movements. However, the pathway by which the cerebellum engages brainstem substrates underlying these movements is not well understood. We used tract-tracing techniques in mice to show that neurons in the medial deep cerebellar nucleus (mDCN) project directly to these putative substrates. Injection of an anterograde tracer into the mDCN produced terminal labeling in the ventromedial medullary reticular formation, which was stronger on the contralateral side. Correspondingly, injection of retrograde tracers into these same areas resulted in robust neuronal cell labeling in the contralateral mDCN. Moreover, injection of two retrograde tracers at different rostral - caudal brainstem levels resulted in a subset of double-labeled cells, indicating that single mDCN neurons collateralize to multiple substrates. Using an awake and behaving recording preparation, we show that spiking activity in mDCN neurons is correlated with respiratory and orofacial behaviors, including whisking and fluid licking. Almost half of the recorded neurons showed activity correlated with more than one behavior, suggesting that these neurons may in fact modulate multiple brainstem substrates. Collectively, these results describe a potential pathway through which the cerebellum could modulate and coordinate respiratory and orofacial behaviors.